Solar light sensitive photodiode produced using a coumarin doped bismuth oxide composite - Dere, A.; Soylu, M.; Yakuphanoğlu, Fahrettin (Elsevier Sci Ltd, 2019)
This article presents a simple and effective method to produce a heterojuction photodiode based on coumarin doped bismuth oxide (Bi2O3) composite. The photoresponse properties of the Au/coumarin doped Bi2O3/p-Si/Al heterojunction can be controlled by applying a voltage and light. The tunable ON and OFF states of the coumarin doped bismuth oxide composite photodiode can be turned into a light-switchable resistive switching. The surface morphology of Bi2O3 doped coumarin thin film was examined using field emission scanning electron microscopy (FESEM). Some of the important electronic parameters such as rectification ratio (RR), ideality factor (n) and the engineered Schottky barrier height (phi(B)) were calculated. The capacitance-voltage-frequency measurements showed that the capacitance of the photodiodes depended on voltage and frequency. The results show that the fabricated devices have a photocapacitive behavior which depends on the doping level of coumarin in Bi2O3 .It was observed that the photocapacitance of the diode decreased with increasing doping level of coumarin upto 10%. This work demonstrated that more attention should be paid on the influence of coumarin dye on the Bi2O3 and/or other metal oxides for the future fabrication of the photodiodes and optical switching device.
Keywords: Sol-gel technique; Coumarin doped Bi2O3; Photoconductive; Photodiode-organic/inorganic Schottky barrier